2004
DOI: 10.1007/bf03027424
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural change in gravity cast Mg−Ni alloys with Ni contents

Abstract: The effects of Ni content on the microstructures of gravity cast Mg-Ni alloys were examined. Different shapes of primary solid particles and microstructures of the eutectic matrix were observed with varying Ni content. The eutectic matrix in the hypoeutectic alloy consisted of rod-like Mg2Ni phase with a small amount of α-Mg phase. The eutectic matrix in the near-eutectic and hypereutectic alloys consisted of eutectic cells oriented in different directions. A transition of lamellae to fiber occurred. The forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…There are many secondary phases observed along the grain boundaries. As per the XRD results and literature survey, the Mg 2 Ni phase is present in Mg-Ni alloys[15,[26][27][28]. As seen in figures 1(a)-(c), with increasing nickel content shapes, the amount and distribution of secondary phases progressively changed.…”
supporting
confidence: 59%
“…There are many secondary phases observed along the grain boundaries. As per the XRD results and literature survey, the Mg 2 Ni phase is present in Mg-Ni alloys[15,[26][27][28]. As seen in figures 1(a)-(c), with increasing nickel content shapes, the amount and distribution of secondary phases progressively changed.…”
supporting
confidence: 59%
“…Magnesium (Mg) alloys are prospective lightweight (density~1.78 g/cm 3 ) materials and possess a high strength-to-weight ratio and high machinability [1][2][3]. However, these alloys are comprised of hexagonal close packed (HCP) crystal structures and have an inadequate c/a ratio [4][5][6][7][8][9][10]. The complex shape component of thermomechanical-processed wrought alloys cannot be designed due to very complex deformation (different mode of twinning, twinning variants, twinning morphology and twinning types [11]) and limited-slip activity under ambient temperature loading.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the set up of Mg-Ni binary alloys has continued, as it was reported that Ni improves the hydriding/dehydriding kinetics and decreases the working temperature dramatically compared to that of pure Mg [17]. Several studies have focused on changes in the hydriding/dehydriding properties of Mg-Ni binary alloys with compositional changes as well as with processing variables [18][19][20]. In fact, hydriding properties of nanostructured materials are different from those of crystalline or amorphous ones, with respect to both thermodynamic and kinetic aspects, as reported by Miitschele and Kirchheim [21].…”
Section: Introductionmentioning
confidence: 99%